282 Reducing the iatrogenicity of neuroleptics in patients with Alzheimer's disease. (23rd September 2015) - Desplanques-Leperre, A; Riolacci-Dhoyen, N; Erbault, M; Banaeï-Bouchareb, L; Chan-Chee, C; Deligne, J; Corre, V Le; Ricordeau, P; Lavallart, B
Abstract : Background and Objectives: Neuroleptics (NL) are often prescribed to patients with Alzheimer's disease (AD), mainly for behaviour disorders and during episodes of confusion. However, these drugs are known to have frequent and severe iatrogenic effects: treating 1000 patients with behaviour disorders receiving NL for 12 weeks would result in 10 additional deaths, 18 strokes (half of which were severe), additional 58 to 94 cases of gait disorders and only 91 to 200 decrease in behaviour disorders. In fact, all AD patients will present behaviour disorders at some time or other. The French Alzheimer public health plan aims to reduce the avoidable iatrogenic effects of NL. Program: The national cooperative group for the optimisation of the prescription of psychotropic drugs in the elderly was established at the initiative of HAS. Its members include nurses, patients, insurers and institutions. A problem-solving approach centred on the patient pathway that included three quality dimensions (Efficacy (E), Safety (S) and Access to best care (A)) was used to develop and implement the tools to achieve an integrated programme going 'from practice improvement to clinical impact measurement'. The practice improvement part which is aimed at reducing the iatrogenic effects of NL in AD patients includes: (1) identification of AD patients with NL (local warning signal=percentage of AD patients taking NL). This indicator is easy to measure in all care sectors and comes with a good practice indicator 'absence of daytime sedation' and monitoring of prescriptions for other psychotropic drugs to prevent drug switching, (2) review of prescriptions for identified AD patients in order to correct inappropriate prescriptions (local indicator for risk containment=percentage of prescriptions reviewed for AD patients), and (3) two new guidelines on behaviour disorders in AD patients and on confusion in the elderly that describe proper use of NL and other psychotropic drugs (E, S) as well as new nondrug techniques of care (A). Reduction of exposure to NL before and after prescription is based on these guidelines. Clinical impact is given by the national rate of exposure of AD patients to NL and is measured in the French AD patient population covered by the three main sickness funds. Results: The first national measures in 2007 on 400 000 AD patients showed that exposure to NL in AD patients was five times higher (16.95%) than in the general population of the same age (2.9%). One year after the Alzheimer plan was launched and after raising the awareness of families and health professionals to the risks of NL, exposure had fallen slightly to 16.1% (equivalent to 3500 fewer cases of exposure). The above programme is in the process being implemented. Results for the national warning signal have been widely diffused. The programme is supported by training initiatives and information campaigns aimed at the general public, the families of AD patients, and health professionals. These are being conducted by the Alzheimer Plan, HAS and professional colleges. Discussion and Conclusion: The above programme is federating doctors, nurses, patients, families and health institutions. Contexte—objectif: Les neuroleptiques (NL) sont souvent prescrits chez les malades Alzheimer (MA), dans les troubles du comportement principalement, et lors d'épisodes de confusion. La iatrogénie fréquente et sévère des NL est aujourd'hui bien documentée: le traitement de 1000 malades avec troubles du comportement traités par antipsychotiques atypiques (NL) pendant 12 semaines résulte en : 10 décès supplémentaires, 18 accidents vasculaires cérébraux dont la moitié sévère, 58 à 94 patients avec troubles de la marche, pour seulement 91 à 200 patients avec diminution des troubles du comportement. Or tous les malades souffrant de MA présenteront au décours de leur maladie des troubles du comportement: la réduction de la iatrogénèse évitable des NL constitue un des objectifs prioritaires du plan de santé public Alzheimer. Programme: Le groupe national de coopération pour l'optimisation de la prescription des psychotropes chez le sujet âgé a été constitué à l'initiative de la HAS et associe soignants, patients, assureurs et institutions. Une analyse de résolution de problème centrée sur le parcours du patient, intégrant les dimensions qualité Efficacité (E) Sécurité (S) et Accès aux meilleurs soins (A), a permis d'élaborer et mettre en œuvre les outils pour un programme intégré depuis l'amélioration des pratiques jusqu'à la mesure d'impact clinique. Le programme national d'amélioration des pratiques vise à réduire la iatrogénèse des NL chez le MA. Il est fondé sur (i) le repérage des MA sous NL (indicateur local d'alerte iatrogénique=% MA sous NL) facilement mesurable quel que soit le secteur de soins, assorti d'un indicateur de bonne pratique sur l'absence de toute sédation diurne, et du suivi des autres psychotropes afin de prévenir les reports de prescription.; (ii) la revue de la prescription des MA repérés pour modifier les prescriptions inappropriées (indicateur local de maitrise du risque iatrogénique=% revue de prescription des MA repérés) (iii) deux nouvelles recommandations sur les troubles du comportement du MA et sur la confusion du sujet âgé - incluant la juste place des NL et autres psychotropes (E, S) et les nouvelles techniques de soins non médicamenteuses (A) – supportent la réduction de l'exposition aux NL en amont comme en aval de la prescription. La mesure de l'impact clinique est réalisée au niveau national par le taux d'exposition des MA aux NL, mesuré sur l'ensemble de population MA française des 3 principaux régimes de l'assurance maladie. Résultats: Les premières mesures nationales 2007 sur près de 400 000 MA confirment une exposition aux NL 5 fois supérieure (16, 95%) à la population générale du même âge (2, 9%). Un an après le lancement du plan Alzheimer et la sensibilisation des familles et professionnels de santé aux risques des NL, ce taux est en légère décroissance (16.1%, ce qui équivaut à 3500 expositions évitées). En parallèle tous les éléments du programme intégré de lutte contre la iatrogénie des NL se mettent en place, avec une diffusion - notamment des résultats de l'indicateur d'alerte national - largement soutenue par les actions de formation et information auprès du grand public, des familles et des professionnels de santé réalisées par le Plan Alzheimer, la HAS et les Collèges professionnels. Discussion et conclusion: Ce programme intégré fédère soignants, patients, familles et institutions sanitaires, et bénéficie d'un indicateur d'alerte national déclinable sur le terrain et compréhensible par tous, des tutelles au grand public. Les résultats à 1 an sont encourageants. Ce programme devrait permettre d'ici 2014 de réduire la prescription appropriée de NL chez le MA aux alentours de 5%, taux estimé au regard de la prévalence des pathologies psychotiques.